Macro-engineering Seawater in Unique Environments Arid Lowlands and Water Bodies Rehabilitation - Badescu, Viorel; Cathcart, Richard B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The subjects refer to histories of ancient and modern use of seacoasts; possible macro-projects capable of massive changes in the coastlines of the Dead Sea, Red Sea and Persian Gulf caused by canal and massively scaled hydropower dam installations; relevant macro-projects for the Black Sea and Baltic Sea; possibilities of refreshment of the Aral Sea and Iran$1 (Bs Lake Uremia with seawater or river freshwater importation macro-projects; potential rehabilitation of some vital arid zone regions now dominated by moving or movable surface granular materials using unique and unusual macro-projects; seawater flooding of land regions situated below present-day global sea-level; harnessing energy and obtaining freshwater from the world$1 (Bs salt-laden ocean by modern industrial means; various macro-projects designed specifically for the protection (reduction of vulnerability) of particular Earth geographical regions.s
Living with Sea Level Change and Dynamic Landscapes -- The Red Sea - Dead Sea Canal -- The Sea Highway Macro-project -- Sediment Transport by Wind and Water -- Macro-engineering Lake Eyre with Imported Seawater -- The Bering Strait Seawater Deflector.
Keywords: Environmental sciences; Sustainable development; Marine Sciences; Environment; Marine & Freshwater Sciences; Sustainable Development; Environmental Monitoring/Analysis.